Navigating Modernity through Adaptive Leadership in Indonesian Islamic Boarding School Education - Mahmudi, Rois; Aimah, Siti (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
This study aims to analyze the forms and characteristics of adaptive leadership at the Darussalam Islamic Boarding School in Blokagung, Banyuwangi, in responding to the challenges of modernity. Employing a qualitative case study approach, data were collected through in-depth interviews with key stakeholders, including leaders, administrators, teachers, and students; participant observation; and the analysis of institutional documents such as policies, curricula, and archival records. Data analysis followed the interactive model proposed by Miles and Huberman, encompassing data reduction, data display, and conclusion drawing and verification, with trustworthiness ensured through the triangulation of sources, methods, and observers. The findings indicate that adaptive leadership contributes significantly to the development of Islamic education management by balancing tradition and modernity through pedagogical innovation, the integration of digital technology, and the strengthening of students’ soft skills. In practical terms, the adoption of digital media, the promotion of entrepreneurship through pesantren -based business units, and the establishment of the Darussalam Economic Cooperation (DASSCO) have enhanced institutional autonomy while generating tangible benefits for the welfare of the surrounding community and alumni. Moreover, the flexibility of the LBKD caregiving system represents an important innovation in fostering a more humanistic and context-sensitive educational environment. Despite these contributions, this study is limited by its lack of in-depth exploration of internal challenges, such as resistance to change and unequal access to digital resources among santri. Future research is therefore recommended to examine international collaboration, the sustainability of pesantren -based enterprises, and the long-term impact of adaptive leadership on the character formation of santri. Overall, this study contributes to the development of a hybrid leadership model that preserves traditional Islamic values while promoting innovation, thereby enabling Islamic boarding schools to remain relevant and globally competitive. Abstrak: Penelitian ini bertujuan menganalisis bentuk dan karakteristik kepemimpinan adaptif di Pondok Pesantren Darussalam Blokagung Banyuwangi dalam menghadapi tantangan modernitas. Menggunakan pendekatan kualitatif jenis studi kasus, data diperoleh melalui wawancara mendalam dengan subjek penelitian pimpinan, pengelola, ustadz, dan santri, observasi partisipan, serta dokumentasi kebijakan, kurikulum, dan arsip kelembagaan. Analisis data mengikuti model interaktif Miles dan Huberman, meliputi reduksi, penyajian, dan penarikan kesimpulan, dengan keabsahan dijamin melalui triangulasi sumber, metode, dan pengamat. Hasil penelitian menunjukkan kepemimpinan adaptif berkontribusi pada pengembangan manajemen pendidikan Islam dengan menyeimbangkan tradisi dan modernitas melalui inovasi pembelajaran, pemanfaatan teknologi digital, serta penguatan soft skills santri. Secara praktis, penerapan media digital, kewirausahaan melalui unit usaha pesantren, dan pembentukan Darussalam Economic Cooperation (DASSCO) memperkuat kemandirian pesantren sekaligus berdampak nyata pada kesejahteraan masyarakat dan alumni. Fleksibilitas sistem pengasuhan LBKD juga menjadi inovasi penting dalam membangun pendidikan humanis dan kontekstual. Keterbatasan penelitian ini adalah belum mendalami tantangan internal, seperti resistensi terhadap perubahan dan keterbatasan akses digital santri. Untuk penelitian selanjutnya, disarankan mengkaji kolaborasi internasional, keberlanjutan usaha pesantren, serta dampak jangka panjang kepemimpinan adaptif terhadap pembentukan karakter santri. Penelitian ini berkontribusi pada pengembangan model kepemimpinan hibrida yang menjaga nilai tradisional Islam sekaligus mendorong inovasi agar pesantren tetap relevan dan berdaya saing global.